If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + (6 + y) = 12 Remove parenthesis around (6 + y) 2y + 6 + y = 12 Reorder the terms: 6 + 2y + y = 12 Combine like terms: 2y + y = 3y 6 + 3y = 12 Solving 6 + 3y = 12 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3y = 12 + -6 Combine like terms: 6 + -6 = 0 0 + 3y = 12 + -6 3y = 12 + -6 Combine like terms: 12 + -6 = 6 3y = 6 Divide each side by '3'. y = 2 Simplifying y = 2
| x-8=6x-13 | | B^5=368 | | 2x+3=51-2x | | 2x+18-4x+12=-6 | | -2=2+(.25)v | | 4(3+c)=3(c-5) | | (x-3).6(x+1)=65 | | 9+(-2)=4+t | | 7x+1=31+4x | | 0.60x+.05(4-x)=.10(-20) | | 3(2x+6)=-6 | | 2m-9-8m=27 | | 6-2(4-8x)=2(3x-5) | | 2.5=d-(20) | | x-(3x+7)=11 | | x-6=-12+2x | | 2.5=d-(.20) | | -9+5x=-5x+1 | | 6.8x-15.3+4.2x=6.4+12x | | b=85+(23)w | | x+8=5x+52 | | 7x+19+-2x=55 | | -3x-5=-47+4x | | 5m-2(4m-1)=-14 | | 10=3x-5x+6 | | x-5-8x=16 | | -14x-4(2x-5)=9 | | -x+6+2x=13 | | 18=8-6b | | (30+5x)+(10x+15)=180 | | (x+6)(3x+8)=0 | | -1-5x+3x=1 |